Des lectures et des écritures du texte littéraire en langue étrangère - Victoria Béguelin-Argimón (Recherches en didactique des langues et des cultures)
Taking into account the difficulties of reading litterature in FL, this article proposes some ressources aimed to facilitate the reading of long litterary texts (such as novels) in FL to students having a confirmed B1 or a B2 level. The possibility of choosing the text to be read, the dialogue between text and reader through writting, or free reading are presented, among other activities, as motivating and easing ways to have access to litterary texts in FL. Propositions are illustrated by some examples taken from a didactic sequence created to read the novel El lápiz del carpintero by the Spanish writer Manuel Rivas in a class of Spanish as a foreign language.